Peran Pendidikan Islam dalam Konteks Penanaman Nilai-Nilai Demokrasi - Martoyo Martoyo; Rino Pambudi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Islamic education has a strategic role in shaping the character and morals of students in line with the principles of democracy. This article aims to examine how democratic values ​​such as equality, justice, deliberation, and tolerance can be instilled through the process of Islamic education, both formally in educational institutions and in non-formal contexts such as religious studies and socio-religious activities. With a qualitative descriptive approach and literature study, this study shows that Islamic education can be an effective instrument in instilling democratic values ​​through the integration of religious teachings, teacher role models, and strengthening the curriculum that encourages dialogue, freedom of thought, and respect for differences. Instilling democratic values ​​in Islamic education is not only relevant to the development of national character, but also becomes an important foundation in forming a civilized civil society.